A novel compact CPW tunable stop band filter using a new Z-DGS-resonator for microwave applications - Elmahjouby Sghir; Ahmed Errkik; Jamal Zbitou; Larbi El abdellaoui; Abdelali Tajmouati; Mohamed Latrach (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The paper presents a novel very compact CPW bandstop filter. The designed structure consists of one unit of new Z-DGS resonator, placed on top layer of ground plane between the input and output this structure, which is excited by 50 ohm coplanar line. The designed filter can be used in X-Band applications as the band stop can be shifted to any other desired frequency by tuning the length of the Z-DGS. The proposed filter topology has as benefits good performances in terms of wide stop-band rejection, low insertion loss, high return loss, simple design and more small size (17.908 × 10 mm2) compared to other previous works those reported in literature. The stop-band width is from 3.96GHz to 6.21GHz, exhibits a 22,25 dB rejection bandwidth of 45% with high selectivity characteristic at the center frequency of 5.05 GHz.